Peningkatan Kualitas Hidup Lansia melalui Program Senam Lansia Terstruktur (Senam Ceria) dengan Pendekatan Edukasi Interaktif Berbasis Komunitas - Sri Wahyuni; Mona Megasari; Ade Ira Maulida; Jasmine Citra Lestari; Cyndy Sri Wahyuni (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2026)
The increasing number of older adults requires promotive and preventive efforts to maintain quality of life, as aging is associated with declines in physical, psychological, and social functioning. Preliminary observations in RW 13, Leuwigajah Village, South Cimahi District, revealed that many older adults did not engage in regular physical activity and had limited knowledge regarding safe and appropriate exercise. This program aimed to improve older adults’ knowledge through a Structured Elderly Exercise Program (Senam Ceria) integrating health education and direct practice. A quasi-experimental one-group pretest–posttest design was employed. The intervention consisted of health education sessions, interactive discussions, structured exercise practice, and leaflet distribution. A total of 11 older adults participated in the program. Data were analyzed using descriptive statistics and the Wilcoxon Signed-Rank test. The results demonstrated an increase in the mean knowledge score from 77.27 ± 8.28 in the pre-test to 97.27 ± 4.67 in the post-test. The Wilcoxon test indicated a statistically significant difference (p = 0.003). The distribution of knowledge categories improved from 45% “good” and 55% “moderate” at pre-test to 100% “good” at post-test. The Structured Elderly Exercise Program (Senam Ceria) was proven effective in enhancing knowledge, participation, and awareness of the importance of regular physical activity among older adults. The program is recommended for sustainable implementation as part of community-based elderly health promotion initiatives.